Pengaruh Manajemen Kesiswaan Terhadap Hasil Belajar Mata Pelajaran SKI Siswa Kelas VIII E MTsN Sambirejo Banyuwangi Tahun Pelajaran 2016/2017 - Ribut Suprapto (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
This research is directed to 3 main points, that is (1) How is the application of student management of VIII E class student in MTsN Sambirejo in academic year 2016/2017? (2) How is the result of learning of VIIIE class student of MTsN Sambirejo of academic year 2016/2017? (3) Is there an influence of student management application to student learning result of class VIII E MTsN Sambirejo year lesson 2016/2017? (4) How big is the influence of student management application to student learning result of class VIII E MTsN Sambirejo academic year 2016/2017 ?. This research uses the quantitative descriptive method with product moment technique. Popoulasi this research is a student of class VIII E MTsN Sambirejo which amount to 33. After doing an analysis of data collected found that (1) Influence Application of student management in MTsN Sambirejo good. (2) The result of the influence of student management application in class VIII E MTsN Sambirejo good. (3) Influence of student management application to learning result VIII E at MTsN Sambirejo exist. (4) the influence of student management implementation on student learning result of class VIII E at MTsN Sambirejo equal to 19,1%